The effect of 1,3-Butanediol on cycling time-trial performance - Shaw, D. M.; Merien, F.; Braakhuis, A.; Plews, D.; Laursen, P.; Dulson, D. K. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
This study investigated the effect of the racemic ß-hydroxybutyrate (ßHB) precursor, R,S-1,3-butanediol (BD), on time-trial (TT) performance and tolerability. A repeated-measures, randomized, crossover study was conducted in nine trained male cyclists (age, 26.7 ± 5.2 years; body mass, 69.6 ± 8.4 kg; height, 1.82 ± 0.09 m; body mass index, 21.2 ± 1.5 kg/m2; VO2peak,63.9 ± 2.5 ml·kg-1·min-1; Wmax, 389.3 ± 50.4 W). Participants ingested 0.35 g/kg of BD or placebo 30 min before and 60 min during 85 min of steady-state exercise, which preceded a ~25- to 35-min TT (i.e., 7 kJ/kg). The ingestion of BD increased blood D-ßHB concentration throughout exercise (0.44-0.79 mmol/L) compared with placebo (0.11-0.16 mmol/L; all p < .001), which peaked 1 hr following the TT (1.38 ± 0.35 vs. 0.34 ± 0.24 mmol/L; p < .001). Serum glucose and blood lactate concentrations were not different between trials (all p > .05). BD ingestion increased oxygen consumption and carbon dioxide production after 20 min of steady-state exercise (p = .002 and p = .032, respectively); however, no further effects on cardiorespiratory parameters were observed. Within the BD trial, moderate to severe gastrointestinal symptoms were reported in five participants, and low levels of dizziness, nausea, and euphoria were reported in two participants. However, this had no effect on TT duration (placebo, 28.5 ± 3.6 min; BD, 28.7 ± 3.2 min; p = .62) and average power output (placebo, 290.1 ± 53.7 W; BD, 286.4 ± 45.9 W; p = .50). These results suggest that BD has no benefit for endurance performance.